Pengaruh Penerapan Corporate Governance terhadap Kinerja Keuangan Perusahaan dengan Ukuran Perusahaan dan Current Ratio sebagai Variabel Kontrol - Bernadette Devina Taufik; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to examine the influence of corporate governance implementation on financial performance. This study also examine the influence of firm size and current ratio on financial performance as control variable. The data were obtained from firms that listed in Corporate Governance Perception Index (CGPI) organized by the Indonesian Institute for Corporate Governance (IICG) during 2001-2015. Corporate Governance was measured by CGPI score. Financial performance was measured by ROE and firm size was measured by Total Assets.The results showed that there was a significant positive influence of corporate governance and financial performance. Furthermore, this study also found that firm size and current ratio had no significant affect on financial performance.